Effect of omeprazole on intragastric bacterial counts, nitrates, nitrites, and N-nitroso compounds. Issue 4 (April 1994) - Verdu, E; Viani, F; Armstrong, D; Fraser, R; Siegrist, H H; Pignatelli, B; Idström, J P; Cederberg, C; Blum, A L; Fried, M
Abstract : Previous studies have suggested that profound inhibition of gastric acid secretion may increase exposure to potentially carcinogenic N-nitroso compounds. The aim of this study was to find out if the proton pump inhibitor omeprazole (20 mg daily) is associated with increased concentrations of potentially carcinogenic N-nitroso compounds in gastric juice. The volume of gastric contents, number of bacteria, and concentrations of nitrates, nitrites, and N-nitroso compounds was determined in gastric aspirates obtained after an overnight fast in 14 healthy volunteers (7M:7F) after one week of treatment with placebo, and one and two weeks' treatment with omeprazole. Median bacterial concentrations were 1.0 x 10(4) (range 5.0 x 10(3)-5.0 x 10(6)) colony forming units (CFU)/ml after one weeks' treatment with placebo and increased significantly to 4.0 x 10(5) (0-3.3 x 10(7)) CFU/ml after two weeks' treatment with omeprazole (p < 0.05). A similar increase was seen in the concentration of nitrate reducing bacteria. There was no difference in the volume of gastric aspirates after treatment with omeprazole when compared with placebo (65 (29-155) ml v 42 (19-194) ml). The concentration of N-nitroso compounds was 0.13 (0-1.0) mumol/l after two weeks of omeprazole, which was not significantly different from that seen with placebo (0.15 (0-0.61) mumol/l). There was also no increase in the concentrations of nitrates or nitrites. It is concluded that omeprazole (20 mg once daily) for two weeks in healthy volunteers is associated with gastric bacterial proliferation but does not increase concentrations of N-nitroso compounds.